Vzroki za osip v ambulantni obravnavi odvisnih od alkohola - Židanik, Miloš (Zdravstveno varstvo, 2006)
Background: Out-patient treatment of alcoholics is characterized by high patient drop out, generally interpreted as resumption of alcohol abuse. The purpose of this survey was to test this hypothesis. Methods: A semi-structuredquestionnaire was sent to 120 individuals with alcohol dependence, who dropped out at different stages of the therapeutic programme. The questionnaire addresed the current use of alcohol in the target population, the reasons for patient drop out and the possibilities for re-entering the programme. Results: The response rate was 26.7 per cent (32 respondents). A relatively high proportion of respondents reported abstinence (19 or 15.8% of the whole sample, n=120) and non-problem drinking (20.8% of the whole sample). The reasons for drop out included passivity, lack of time, problems in the therapist-patient relationship, resistance in the patients family and change in the therapeutic setting (hospitalisation). Conclusions: The results obtained made us change our attitude to patient drop out and revise our therapeutic strategies.
Keywords: Alcoholism; alkoholiki; Alkoholizem; Ambulantna oskrba; Ambulatory Care; Bolniki, osip; odvisnost; Patient Dropouts; Therapy; zdravljenje